The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.11646/zootaxa.5297.4.3
|View full text |Cite
|
Sign up to set email alerts
|

An annotated checklist of terrestrial flatworms (Platyhelminthes: Tricladida: Geoplanidae) from Mexico, with new records of invasive species from a citizen science platform and a new nomen dubium

Abstract: A checklist of species of terrestrial flatworms (Platyhelminthes: Tricladida: Geoplanidae) recorded for Mexico is compiled, listing 11 species. Five are directly referenced in the literature: Bipalium kewense Moseley, 1878, Bipalium vagum Jones & Sterrer, 2005, Diporodemus yucatani Hyman, 1938, Geoplana multipunctata Fuhrmann, 1914, and Pseudogeoplana nigrofusca (Darwin, 1844); and one species had been indirectly mentioned for the country: Parakontikia ventrolineata (Dendy, 1892), which was described from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…Recently, there have been numerous reports of occurrence of the invasive predatory flatworms (Geoplanidae) across the world. New records of the hammerhead flatworms Bipalium kewense Moseley, 1878 and Bipalium vagum Jones & Sterrer, 2005 (Platyhelminthes, Geoplanidae, Bipaliinae) have been reported from several states in Mexico [2,5,6], Italy [7,8], Canada [9], Cuba [10], Barbados, Colombia, Costa-Rica, El Salvador, Indonesia, Madagascar, Malaysia, Mauritius, Mexico, Puerto Rico, Tahiti, Taiwan and Zimbabwe [2,11]. Brown et al [12] reported the occurrence of Bipalium vagum as well as other exotic terrestrial flatworms from Jamaica.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have been numerous reports of occurrence of the invasive predatory flatworms (Geoplanidae) across the world. New records of the hammerhead flatworms Bipalium kewense Moseley, 1878 and Bipalium vagum Jones & Sterrer, 2005 (Platyhelminthes, Geoplanidae, Bipaliinae) have been reported from several states in Mexico [2,5,6], Italy [7,8], Canada [9], Cuba [10], Barbados, Colombia, Costa-Rica, El Salvador, Indonesia, Madagascar, Malaysia, Mauritius, Mexico, Puerto Rico, Tahiti, Taiwan and Zimbabwe [2,11]. Brown et al [12] reported the occurrence of Bipalium vagum as well as other exotic terrestrial flatworms from Jamaica.…”
Section: Introductionmentioning
confidence: 99%